Draft Ninth Five Year Plan (1997-2002) and Annual Plan 1997-98 (Volume I) National Capital Territory of Delhi - Planning Commission (Planning Commission, 1997)
The Ninth Plan is being launched in the 50th year the Independence of our country. Delhi, the Capital of the country has to present a model to be emulated by others. On the Ninth Five Year Plan the main emphasis has been laid an expansion of infra structure network under core sectors well as social sectors. While formulating the Ninth Plan efforts have also been made to fill up the gaps identified in the implementation of Eighth Five Year Plan.
Planning Department, Govt of N.C.T of Delhi